P04.20 The role of YAP in Glioblastoma cell lines. (9th September 2021) - Casati, G; Giunti, L; Iorio, A; Marturano, A; Sardi, I
Abstract: BACKGROUND: Glioblastoma (GBM) is a primary human malignant brain tumor, the most common in adults. Several studies have highlighted the Hippo-pathway as a cancer signalling network. The Hippo pathway is an evolutionarily conserved signal cascade, which is involved in the control of organ growth. Dysregulations among this pathway have been found in lung, ovarian, liver and colorectal cancer. The key downstream effector of the Hippo-pathway is the Yes-associated protein (YAP); in the nucleus, its function as transcription co-activator is to interact with transcription factors, resulting in the expression of target genes involved in pro-proliferating and anti-apoptotic programs. MATERIAL AND METHODS: Using western blotting analysis, we determined the nuclear expression of YAP on three GBM cell lines (U87MG, T98G and A172). To investigate which inhibitors against the Hippo-pathway were the most efficient, we performed a cytotoxic assay: we treated all the three cell lines with different inhibitors such as Verteporfin (VP), Cytochalasin D (CIT), Latrunculin A (LAT), Dobutamine (DOB) and Y27632. Afterwards, we performed a treatment using Doxorubicin (DOX) combined with the inhibitors, evaluating its cytotoxic effect on our cell lines, through cell viability experiments. More western blotting experiments were performed to investigate the oncogenic role of YAP at nucleus level. Furthermore, preliminary experiments have been conducted in order to investigate the apoptosis, senescence and autophagy modulation due to the Hippo-pathway. RESULTS: We showed our cell lines express nuclear YAP. We assessed the efficiency of the main inhibitors against Hippo-pathway, proving that VP, LAT A and CIT show a strong cytostatic effect, linked to time increase; plus we saw a cytotoxic effect on T98G. The association of DOX with selected inhibitors is able to reduce cell viability and nuclear YAP expression rate in all three GBM lines. Finally, preliminary experiments were set up to assess how and if the mechanisms of apoptosis, autophagy and senescence were affected by the Hippo-pathway. The combination of DOX with inhibitors promotes resistance to apoptosis. CONCLUSION: Our results show that nuclear YAP is present in all tumor lines, thus confirming that this molecular pathway is functioning in GBM lines. Nuclear YAP is more highly expressed after DOX administration. Moreover, the combined treatment (DOX with Hippo-pathway inhibitors) reduces both cell proliferation and viability, and increases the rate of apoptosis. Preliminary experiments on senescence and autophagy were used to determine the best Hippo-pathway inhibitor. These data demonstrate that the Hippo-pathway plays a crucial role in GBM proliferation and resistance to apoptosis. Inhibiting this pathway and in particular the transcription factor YAP, in association with DOX, might be an excellent therapeutic target.